INTERNAL COMMUNICATION AS A KEY TO EFFICIENCY: CHALLENGES, ISSUES, AND SOLUTIONS IN THE AGRICULTURAL BUSINESS - Syniuk , О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2025)
The article highlights the importance of internal communication as one of the fundamental factors for the effective functioning of agricultural enterprises amid the transformation of Ukraine’s agrarian sector. The author emphasises that internal communication is not merely an information exchange process, but a strategic resource that determines the level of an organisation, adaptability and competitiveness of an enterprise. The research systematises the main functions of internal communication, including coordination between departments, prompt decision-making, increased labour productivity, formation of corporate culture, ensuring safety, reducing staff turnover, and fostering innovation. The study presents a structured analysis of the challenges and problems faced by agricultural enterprises in establishing effective communication. These include geographical dispersion of facilities, diverse workforce composition, seasonal nature of production, cultural differences, lack of standardised information exchange procedures, psychological barriers between staff and management, intergenerational communication gaps, and financial constraints. Based on these challenges, practical recommendations are proposed, such as the digitalisation of communication processes, the use of modern IT tools, implementation of ERP systems, regular training sessions, standardisation of information exchange, and the development of an open corporate culture. Special attention is given to the classification of modern internal communication tools (messengers, cloud services, video conferencing, intranet portals, feedback boxes, video instructions, etc.) and their advantages in the context of agricultural production. The article concludes that developing a robust internal communication system necessitates a systematic approach, the incorporation of communication into the overall strategy of the organisation, continuous evaluation of the effectiveness of communication channels, and a preparedness for organisational change. A thorough understanding of communication's significance not only facilitates timely managerial decisions but also strengthens the overall resilience of agribusiness in a dynamic external environment.